(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
An audiometer is a medical device that measures hearing state; most audiometers are for manual and physical use. The audio signal generator generates all the frequencies between 20 Hz and 22 kHz. This project will produce a tone-based audiometer (software and hardware) based on the Arduino board with GUI MATLAB. This work allowed us to do the test automatically with intelligent diagnosis. The smart part is based on the Neural Network Model. Our work comprises an electronic card and three parts or interfaces: Interface 1: subject management, Interface 2: hearing test, and Interface 3: audiogram. The tests and results of the prototype are very satisfactory; this is a positive sign that the prototype is working as expected and is a viable solution.